Reusing Minarets as a Passive Cooling (Wind Catcher/Solar Chimney): A Case Study in the Emirate of Sharjah - ABDALLA, TALIB ABDALLA ALI (2023)
The number of mosques in the United Arab Emirates exceeds 9,000 mosques, including approximately 3,000 mosques in the Emirate of Sharjah alone. The minaret accompanies the design of each mosque, which is equivalent to the number of mosques, and more, since some mosque designs have more than one minaret. In this research, the idea of repurposing minarets or adding new uses to them is studied, such as using minarets as a passive cooling method, such as using them as wind catchers/solar chimneys that contribute to the process of directing the wind to the prayer hall and work to increase thermal comfort through environmentally friendly passive cooling methods. The Luqman Mosque in the Al Tay area in Sharjah was studied as a model for a case study. It was drawn using the IESVE computer simulation program, and then different scenarios were created for the idea of creating a connection between the prayer hall and the minaret by making doors and windows. After that, the opening and closing of windows and doors in each case were studied. One side of the prayer hall and the minaret, in addition to scenarios for opening the windows of the dome and adding a divider in the minaret, divides it into two parts. It should be noted that the number of virtual scenarios reaches 34 designs. The results are then analyzed, conclusions are drawn, and the results are then evaluated. The study revealed the possibility, benefit, and feasibility of the idea of repurposing the minaret in reducing overall energy consumption and the impact of thermal comfort elements such as air temperature, relative humidity, wind movement, mean radiant temperature and CFD in the process of repurposing the minaret.